EFICÁCIA ADAPTATIVA E DINÂMICA PSÍQUICA EM ENLUTADOS POR ACIDENTES DE TRÂNSITO ATENDIDOS EM PSICOTERAPIA BREVE OPERACIONALIZADA (PBO) - SERRALHEIRO, REGIANE RIBEIRO DE AQUINO (2019)
Traffic accidents have killed about 43 thousand of people per year and more than 500 thousand injured. In addition to the costs of providing care to fatal and non-fatal victims, there are the social costs and psychological impact on the victims and their families and little has been done to assist the grief. The present study had as objective to evaluate and relate the evolution of the adaptive efficacy and the psychic dynamics of bereaved people for traffic accidents attended in Brief Psychotherapy Operated (PBO), through a qualitative study of a combined method (clinical and quasi-experiment). The participants were submitted to interviews analyzed by the Operative Adaptive Diagnostic System (SISDAO) and the Phillipson's Object Relations Test (TRO), then, were attended in PBO for 12 sessions, being reassessed at the end by the same instruments. The sample consisted of 6 cases, predominantly female and university (83%), with a mean age of 40 years and two (33%) were vehicle drivers. In relation to the deceased, two (22%) were son and two (33%) parents, with a mean age of 40.5 years, (66%) male and (66%) passenger vehicles. In the initial evaluation of TRO, observed predominance of the schizo-paranoid position with alternation of the gliscocárrica, use of mechanisms of more primitive defenses and poor contact with reality. Mourning was considered a problem situation for the PBO and, through theorized interpretations, it sought to aid in the understanding of the solutions given, such as intense persecutory guilt and omnipotent fantasies that might have prevented accidents. In the final evaluation, there was a reduction in the intensity of the crisis, increased confidence in the internal and external world, better contact with reality and evolution in adaptive effectiveness. Both TRO and SISDAO were sensitive to observe changes in psychic dynamics. Finally, it can be stated that patients benefited from PBO and, this type of psychological intervention can help patients with this demand. It is recommended that more studies can be carried out, expanding the sample and it is expected that it can contribute to the debate of public politics of health promotion, accident prevention and, in the event of these, that the mourners in need, can be welcomed in their suffering, so that they can resume their lives and respond more effectively to the demands of daily life.